Optimisation of emulsion-based edible coating and development of coating applicator machine for postharvest life study of guavas (Psidium Guajava L.) / Mohd Zahid Abidin - Abidin, Mohd Zahid (Institute of Graduate Studies, UiTM, 2012)
Application of edible coating represents a method that can extend the shelf life of picked guava by minimising the weight loss mainly due to natural migration process of moisture and gases. Response surface methodology (RSM) was employed to search for best composition of edible coating comprised of three variables namely palm stearin, palm kernel olein and beeswax. The RSM was also used to investigate the influence of temperature of coating emulsion and dipping time on the coating pickup for the optimisation of coating process condition. From the RSM-generated model, optimum coating composition for minimising guava weight loss was 4.5% (w/v) palm stearin, 1% (w/v) palm kernel olein and 1% (w/v) beeswax. The RSM predicted and experimental weight loss (7%) were not significantly different from each other.